2007
DOI: 10.4049/jimmunol.179.6.4153
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Up-Regulates Substance P in Polymicrobial Sepsis-Associated Lung Injury

Abstract: Hydrogen sulfide (H2S) has been shown to induce the activation of neurogenic inflammation especially in normal airways and urinary bladder. However, whether endogenous H2S would regulate sepsis-associated lung inflammation via substance P (SP) and its receptors remains unknown. Therefore, the aim of the study was to investigate the effect of H2S on the pulmonary level of SP in cecal ligation and puncture (CLP)-induced sepsis and its relevance to lung injury. Male Swiss mice or male preprotachykinin-A gene knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 36 publications
2
50
0
1
Order By: Relevance
“…15A). Moreover, NaHS has been suggested previously to increase lung microvascular permeability in sepsis (27). As a result, application of H 2 S donor, to some extent, worsened sepsis-associated mortality, although severe and lethal CLP model was used in the present study ( Fig.…”
Section: Effect Of H 2 S On Sepsis-associated Hepatic Dysfunction Andmentioning
confidence: 78%
“…15A). Moreover, NaHS has been suggested previously to increase lung microvascular permeability in sepsis (27). As a result, application of H 2 S donor, to some extent, worsened sepsis-associated mortality, although severe and lethal CLP model was used in the present study ( Fig.…”
Section: Effect Of H 2 S On Sepsis-associated Hepatic Dysfunction Andmentioning
confidence: 78%
“…Furthermore, SP incites COX-2 and PGE 2 expression in human colonic epithelial cells and HUVECs through the activation of JAK-STAT (15) and MAPK pathways (17), respectively. Given that endogenous H 2 S was known to upregulate SP in sepsis-induced ALI (47) and to regulate inflammatory response in CLP-induced sepsis by activating the ERK1/2 and NFkB pathways (42), there exists the possibility that H 2 S may contribute to sepsis-evoked ALI via the signal transduction pathway of H 2 S-TRPV1-SP-ERK1/2-NF-kB-COX-2-PGEM. Although the exact mechanistic pathway mediating H 2 S induction of COX-2 remains to be investigated, H 2 S and SP may share a common signaling cascade involving the activation of ERK and NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as a therapeutic tool, pharmaceutical-grade Na 2 S shows great potential and has been successfully used to prevent and treat myocardial infarction, ischemia-reperfusion injury and endotoxic shock [112,113]. It is Table 2 By sharp contrast, no effect was observed with mesalamine or ADT-OH treatment alone, suggesting protective effects in addition to H 2 S release [111] Male Wistar rats: Carageenan-induced hindpaw edema The study concluded that the additional anti-inflammatory effect of S-diclofenac was due to H 2 S release [134] Male Wistar rats: Trinitrobenzene sulfonic acid-induced colitis [125] Male Swiss albino mice: Cecal ligation and puncture-induced sepsis PPT-A gene expression and substance P levels whereas NaSH increased substance P levels and lung injury [71] Balb/C mice: Acute pancreatitis and associated lung inflammation induced by cerulein…”
Section: H 2 S Donor Molecules and Inflammation: Notes Of Cautionmentioning
confidence: 99%
“…H 2 S has also been proposed as a novel mediator of neurogenic inflammation. Intraperitoneal injection of NaSH into 'normal' mice induced significant NKR1-dependent, but NKR2-and CGRP-independent, increases in plasma levels of SP and pronounced lung inflammation [70], and in sepsis-induced lung injury [71] and acute pancreatitis [72], H 2 S upregulated plasma levels of SP and aggravated lung inflammation. These effects were blocked by either a selective NK1R antagonist or genetic depletion of PPT-A.…”
Section: Role For H 2 S In Neurogenic Inflammation?mentioning
confidence: 99%